1998
DOI: 10.1177/089198879801100107
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder in Late Life: A Review

Abstract: Although there is a broad base of literature on depression among elderly patients and on mania in younger patients, there is a relative paucity of information on bipolar disorder in the elderly population. While the quantities of data reflect the relative prevalences of these illnesses, there is evidence to suggest that classification of mania in the elderly with respect to age of onset, natural course, family history, and pathophysiology may be useful in understanding the heterogeneous etiologies of this synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…This percentage largely reflects literature findings on the "treated prevalence" rates of elderly mania [8,9]. The reported decrease of the prevalence of manic episodes in late life could be attributed to disorder-related factors (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…This percentage largely reflects literature findings on the "treated prevalence" rates of elderly mania [8,9]. The reported decrease of the prevalence of manic episodes in late life could be attributed to disorder-related factors (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Many of these reviews have been targeted toward the clinician, and they have relied heavily on extrapolating data from other psychiatric disorders in late life or from younger people with bipolar disorder. Reviews that have more systematically critiqued available data need to be updated (30–33).…”
mentioning
confidence: 99%
“…Patient selection criteria. As noted in other reviews of bipolar disorder in older people (30, 32, 33), the definition of age of onset varied widely across studies in several ways, which likely contributes to inconsistency across investigations. Studies varied in whether they reported onset of affective symptoms, full‐blown depression or mania, or psychiatric hospitalization.…”
mentioning
confidence: 99%
“…Menopause is one of the factors that may influence onset, presentation and course of mood disorders in women after 40 years. Family history of mood disorder is less common, and neurological and vascular disorders are commoner in late-onset depression than in early-onset depression [28, 29]. …”
Section: Discussionmentioning
confidence: 99%